Primitive neuroectodermal tumor of prostate - Kumar Vikash; Khurana N; Rathi A; Malhotra Anju; Sharma Kanika; Abhishek Ashu; Bahadur A (Wolters Kluwer Medknow Publications, 2008)
Primitive neuroectodermal tumors (PNETs) are malignant proliferations of small, undifferentiated neuroectodermal cells occurring mainly in children and share the same reciprocal translocation between chromosomes 11 and 22 and the same patterns of biochemical and oncogene expression as osseus and extraosseus Ewing′s sarcoma. Some PNETs occur in the brain, while others (the peripheral PNETs) occur in sites outside the brain, such as in the extremities, pelvis and the chest wall. They mostly originate in the chest, pelvis and retroperitoneum; in rare cases, occurrence in the head and neck area has also been seen. We present a rare case of primitive neuroectodermal tumor arising in the prostate gland in a 25-year-old male. To the best of our knowledge, this is the first documentation of a primary peripheral primitive neuroectodermal tumor in the prostate gland of any patient from India and rarely reported in English literature.